Interleukin-6 mediates low-threshold mechanical allodynia induced by intrathecal HIV-1 envelope glycoprotein gp120 - Schoeniger-Skinner, Diana K. (2007)
Spinal cord glia (microglia and astrocytes) contribute to enhanced pain states. One model that has been used to study this phenomenon is intrathecal (i.t.) administration of gp120, an envelope glycoprotein of HIV-1 known to activate spinal cord glia and thereby induce low-threshold mechanical allodynia, a pain symptom where normally innocuous (non-painful) stimuli are perceived as painful. Previous studies have shown that i.t. gp120-induced allodynia is mediated via the release of the glial pro-inflammatory cytokines, tumor necrosis factor-α (TNF), and interleukin-1β (IL-1). As we have recently reported that i.t. gp120 induces the release of interleukin-6 (IL-6), in addition to IL-1 and TNF, the present study tested whether this IL-6 release in spinal cord contributes to gp120-induced mechanical allodynia and/or to gp120-induced increases in TNF and IL-1. An i.t. anti-rat IL-6 neutralizing antibody was used to block IL-6 actions upon its release by i.t. gp120. This IL-6 blockade abolished gp120-induced mechanical allodynia. While the literature predominantly documents the cascade of pro-inflammatory cytokines as beginning with TNF, followed by the stimulation of IL-1, and finally TNF plus IL-1 stimulating the release of IL-6, the present findings indicate that a blockade of IL-6 inhibits the gp120-induced elevations of TNF, IL-1, and IL-6 mRNA in dorsal spinal cord, elevation of IL-1 protein in lumbar dorsal spinal cord, and TNF and IL-1 protein release into the surrounding lumbosacral cerebrospinal fluid. These results would suggest that IL-6 induces pain facilitation, and may do so in part by stimulating the production and release of other proinflammatory cytokines.